Cyclophilin interactions with incoming human immunodeficiency virus type 1 capsids with opposing effects on infectivity in human cells - Hatziioannou, Theodora; Perez-Caballero, David; Cowan, Simone; Bieniasz, Paul D (Journal of virology, 2005)
Cyclophilin A (CypA) is a peptidyl-prolyl isomerase that binds to the capsid protein (CA) of human immunodeficiency virus type 1 (HIV-1) and by doing so facilitates HIV-1 replication. Although CypA is incorporated into HIV-1 virions by virtue of CypA-Gag interactions that occur during virion assembly, in this study we show that the CypA-CA interaction that occurs following the entry of the viral capsid into target cells is the major determinant of CypA's effects on HIV-1 replication. Specifically, by using normal and CypA-deficient Jurkat cells, we demonstrate that the presence of CypA in the target and not the virus-producing cell enhances HIV-1 infectivity. Moreover, disruption of the CypA-CA interaction with cyclosporine A (CsA) inhibits HIV-1 infectivity only if the target cell expresses CypA. The effect of CsA on HIV-1 infection of human cells varies according to which particular cell line is used as a target, and CA mutations that confer CsA resistance and dependence exert their effects only if target cells, and not if virus-producing cells, are treated with CsA. The differential effects of CsA on HIV-1 infection in different human cells appear not to be caused by polymorphisms in the recently described retrovirus restriction factor TRIM5alpha. We speculate that CypA and/or CypA-related proteins affect the fate of incoming HIV-1 capsid either directly or by modulating interactions with unidentified host cell factors.